Relationship between Job Satisfaction and Turnover Intention: Evidence from Bangladesh - Rahman, Shaikh Moksadur (Asian Business Review, 2020)
Nowadays job satisfaction and turnover intention are the most important and widely researched variables. Job satisfaction increases loyalty and professional commitment to the organization which leads to productivity. On the other hand, the turnover intention has serious negative consequences for effective organizational operations. The purpose of this exploratory study is to find out the relationship between job satisfaction and turnover intention of employees working in some selected sectors in Cumilla, Bangladesh. The study considered a sample of 355 employees across various sectors to find out the different opinions about the levels of their satisfaction related factors and turnover intention. For the purpose of in-depth analysis, statistical tools, inter-correlation matrix, and multiple regression techniques had been used. The results indicate that there was a significant inverse relationship between job security-turnover intention, pay-turnover intention, and promotion-turnover intention. The results will help organizations understand how to address employees’ demands and concerns toward their jobs and discover successful ways of retaining them. This in turn will reduce the turnover rate and the associated costs.